2009
DOI: 10.1063/1.3159736
|View full text |Cite
|
Sign up to set email alerts
|

Ethene stabilization on Cu(111) by surface roughness

Abstract: The molecular vibrations of ethene adsorbed on roughened Cu(111) surfaces have been investigated with high resolution electron energy loss spectroscopy and density-functional-theory calculations. The roughness was introduced by sputtering or evaporation of copper, respectively, on the cooled surface. We found stabilization of the ethene layer compared to ethene adsorbed on pristine Cu(111). Furthermore, two new vibrational features observed on the rough surface can be assigned to frustrated translations and ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 39 publications
3
23
0
Order By: Relevance
“…With HREELS we were able to detect a broad dipoleactive vibrational feature at about 35-40 meV at the roughened surface at 85 K, which characterizes the roughened surface and vanishes after annealing to room temperature. 24 Vibrational features with similar energies are known from stepped surfaces 25,26 and are predicted for adatoms and small islands. 21,27,28 The development of the surface reflectivity for IR light and low-energy electrons, respectively, with increasing roughness is shown in Fig.…”
Section: A Copper On Cu"1 1 1…mentioning
confidence: 79%
“…With HREELS we were able to detect a broad dipoleactive vibrational feature at about 35-40 meV at the roughened surface at 85 K, which characterizes the roughened surface and vanishes after annealing to room temperature. 24 Vibrational features with similar energies are known from stepped surfaces 25,26 and are predicted for adatoms and small islands. 21,27,28 The development of the surface reflectivity for IR light and low-energy electrons, respectively, with increasing roughness is shown in Fig.…”
Section: A Copper On Cu"1 1 1…mentioning
confidence: 79%
“…According to first‐principles calculations within DFT, CC dimers are stable on all sites on a Cu surface. Moreover, carbon dimers containing hydrogen are very unfavorable on a surface with low adsorption energies, even in defects, and desorb or immediately decompose even at very low temperatures, as demonstrated in temperature‐programmed desorption (TPD) and thermal desorption spectroscopy (TDS) experiments . Complementary studies of acetylene (CH≡CH) aromatization over transition metals also demonstrated that the benzene ring is not stable at the metallic surface .…”
Section: Cvd Synthesis and Growth Of Graphenementioning
confidence: 99%
“…As opposed to the CO molecule which is oriented perpendicular to the Cu(111) surface, the C 2 H 4 and CO 2 molecules form almost planar configurations on Cu(111). [44][45][46] The corresponding IETS spectra are represented in Fig. 4, where the positive voltage region (V > 0) corresponds to a realistic vibrational region which includes the sample CO, the tip and the top-most Cu layers, while the negative voltage region (V < 0) shows the results obtained for the imaginative but illustrative case when only the sample side (CO molecule and topmost Cu layer) vibrates.…”
Section: A Aligned Tipsmentioning
confidence: 99%